PELATIHAN OLAHAN IKAN NILA BERNILAI TAMBAH DI DESA KAWALI CIAMIS JAWA BARAT - Saputra, Rahmad Surya Hadi; Napitupulu, Romauli Juliana; Soeprijadi, Liliek; Panjaitan, Pola Sabar Tumohon; Anasri, Anasri; Mukhaimin, Imam (Jurnal Abdi Insani, 2024)
Desa Kawali is one of the Smart Fisheries Villages (SFVs) located in the Kawali District, with its main commodity being tilapia fish. Currently, there are approximately 4,000 fish ponds around the location of Desa Kawali with immense potential. The abundant production of tilapia fish, supported by extensive aquaculture land, can serve as a primary asset in ensuring food security for the village community and also in enhancing their welfare. The welfare of the residents of Desa Kawali largely depends on tilapia fish, which are marketed in the form of live fish or ready-to-consume products. While there is a growing number of processed fish products, the variety and quantity of processed products produced are still limited. Community service is conducted using the Participatory Rural Appraisal (PRA) approach. The PRA method is an approach to community empowerment that emphasizes the involvement or participation of the community in all activities, with external facilitators serving as guides to facilitate community activities. It is a participatory action research method designed to encourage active participation of the community in the development process. The results of the community service activities conducted, ranging from the delivery of materials to practical product manufacturing and packaging, can be summarized as follows: the community service activities conducted provide numerous benefits to the participants. These activities also impact the skills of the participants, and with proper and attractive product packaging, the processed products become more marketable